Annotated legal documents on Islam in Europe / Volume 17 Norway / compiled and annotated by Marianne Bøe - Bøe, Marianne (Annotated legal documents on Islam in Europe, 2019)
Status of religious communities -- Relations between the state and Islam -- State support for Islamic religious communities -- Muslims in integration law -- Mosques and prayer houses -- Burials and cemeteries -- Education -- Further and higher (tertiary) education -- Islamic chaplaincy in public institutions -- Employment and social law -- Islamic slaughter and food regulation -- Islamic goods and services -- Islamic dress -- Criminal law -- Family law